A Study of Diversity Management in Different Companies and Different Sectors - Uttam Sahay, Kavita Saini, Rajwinder Kaur, Dr. Gagandeep Kaur (International Journal of Advanced Science and Technology, 2020)
Managing Diversity is very important now a day’s for each and every organization because of its increasing importance day by day. A diverse workforce always provides different ways to solve the problem. Earlier diversity was considered as a difference in gender, age, religion, caste, and color, etc.  But now a day’s it is regarded as a different style of work, clothing style, the background of the family, sexual orientation and generation gaps, etc. So, the paper analyzes diversity management in different companies and in different sectors in India and their related companies. The importance of implementing diversity in the workplace also discussed in the paper. It also studies how organizations are implementing diversity in their organizations. The research also provides various challenges faced by companies in managing diversity. The paper concludes the various measures and suggestions which the companies can take so that the performance and productivity of the employees get increased by promoting diversity in the organizations.